A Comparative Study of the Irrigated Zones of Jaguaribe-Apodi and Morada Nova from a (Un) Sustainable Perspective (Global Journal of Human-Social Science, 2023)
Large-scale government-sponsored irrigation is a feasible alternative to the development of semiarid regions such as Northeastern Brazil provided perennial rivers and reservoirs are available Brazilian irrigation projects have also generally promoted the participation of farmers as informed agents in the process encouraging training and education towards agribusiness The purpose of this explorative and descriptive study was to analyze and compare the sustainability characteristics of the Jaguaribe-Apodi and Morada Nova irrigation zones in light of the triple bottom line model Elkington 2012 based on information from 18 interviews conducted in September 2015 to November 2015 and submitted to discourse analysis Triple bottom line sustainability envisages a balance between three dimensions social environmental and economic Such a balance was not observed in our study due to insufficient awareness of environmental issues However focusing on a specific context and moment in time the exploratory study design made it difficult to extrapolate our findings Future studies could expand the discussion on the sustainability of irrigation zones by using data triangulation in longitudinal designs
Keywords: semiarid climate subsistence farmer sustainability jaguaribe-apodi irrigation zone morada nova irrigation zone triple bottom line